Effect of body movement practices on motor development in children and adolescents with cerebral palsy (Research, Society and Development, 2021)
Cerebral palsy originates from neurological lesions that appear in three different conditions, according to the injured neuroanatomical region, such as spastic, ataxic and athetoid. Thus, children and adolescents with cerebral palsy have declines in motor control and voluntary movements, the degree of performance shown will be closely related to the severity of the brain injury. The aim of this study was to investigate through a systematic review the influence of different physical and motor interventions on the motor development of children and adolescents with CP. A search was carried out for studies in English and Portuguese produced from 2010 to 2020, in the databases: Pubmed, Lilacs, Scielo, Elsevier and Pedro. In all, 06 studies were described. All studies show improvements in the investigated functions. The findings exposed in the studies found in this review, demonstrate that the effect of body movement practices corroborates positively on the motor development of patients with cerebral palsy. It is suggested that further studies may be carried out that address not only the methods already presented, but new tools that influence the improvement of motor coordination and quality of life of patients with cerebral palsy in all types and topographies.